Research on all-optical redundancy networks underground coal mines. Issue 1 (June 2021) - Zhang, JinHao; Lin, Yin; Chen, Min
Abstract: In view of the serious environmental interference of coal mine underground, the inconvenient power supply of underground equipment and the existence of passive serial series series number of existing F5G underground network network, explore a new coal mine underground all-optical network redundancy technology networking scheme, realize the multi-stage series of passive light branches of the mine, Solve the problem of low number of underground optical branches in series and anti-interference of communication. Based on the principle of all-optical network network, this paper expounds the redundancy protection mechanism of all-optical network group, and designs a wide-ranging coverage scheme of fiber optic whole mine through precision calculation and analysis. Through laboratory verification and coal mine roadway simulation experimental data show that the all-optical redundancy technology network scheme can realize the underground passive light multi-stage serialization, while ensuring the priority and reliability of underground gas system. At the same time, the priority and reliability of the underground gas system are guaranteed; the scheme parameter comparison table is suitable for various types of coal mines and can be used as a reference for coal mine users in the construction of underground all-optical networks.